Hydrogen Sulfide (H2S) Removal by Commercialized Biochar Derived from Rice Husk: Effect of Flowrate, Temperature and Sorbent Weight - Bahari Alias, Azil; Ariff Amir Hamzah, Muhamad; Nur Adibah Hafizah Mohamad, Nik; Fathmi Masor @ Mansor, Mohamad; Abdul Rashid, Zulkifli; Hidayah Meri, Nor; Azwan Abd Rahman, Ashadi; Talib, Norhayati; Azlina Wan Ab Karim Ghani, Wan (International Journal of Engineering and Technology, 2018)
The presence of Hydrogen Sulphide (H2S) is one of the major sources contributing to air pollution nowadays. Hence, proper action should be taken to reduce the emission of H2S to open air. This can be achieved by adsorbing the toxic gas onto adsorbent. The evolution of biochar as an effective adsorbent acted as a precursor to the active carbon, as it uses less energy during its production and has porosity similar to activated carbon. This study has focused on commercialized biochar derived from rice husk produced by local industry, Sendi Enterprise located in Tanjung Karang, Selangor. Characterizations of rice husk and rice husk biochar were determined using Elemental analysis, FTIR analysis, BET analysis and SEM. The effectiveness of commercialized on adsorbing H2S gas was investigated by using as adsorption system at different flowrates, sorbent weights, and process temperature. In the removal of H2S by using different sorbent weight, it was found that higher sorbent weight increased the adsorption rate of H2S. As for flowrate, less flowrate contributed to higher adsorption capacity. Meanwhile, on temperature parameter, it can be verified when system used low temperature, high adsorption capacity was recorded.Â